Asymmetric α-Amination Reaction of Alkenoate Cyclic Esters Catalyzed by Chiral Tin Alkoxides - Yanagisawa, Akira; Yamashita, Yoshiki; Uchiyama, Chika; Nakano, Ryuta; Horiguchi, Moe; Ida, Kazuki (Synlett, 2019)
A catalytic enantioselective α-amination reaction of alkenoate cyclic esters with dialkyl azodicarboxylates was achieved by using a 3,3′-di(1-naphthyl)-substituted (R)-BINOL–dibromostannane complex as a chiral precatalyst in the presence of a sodium alkoxide and an alcohol. Optically active α-hydrazino ketones were obtained in moderate to high yields and with up to 91% ee in the presence of the chiral tin alkoxide generated in situ.
Keywords: alkenoate cyclic esters; lactones; amination; asymmetric catalysis; dialkyl azodicarboxylates; tin catalysis